Intra and Inter-specific Variability of Salt Tolerance Mechanisms in Diospyros Genus - Gil-Muñoz, Francisco; Pérez-Pérez, Juan Gabriel; Quiñones, Ana; Naval, María del Mar; Badenes, María Luisa (Frontiers in Plant Science, 2020)
Saline stress is one of most important problems that agriculture must face in the context of climate change. In the Mediterranean basin, one of the regions most affected, persimmon production can be compromised by this effect, due to the limited availability of salt tolerant rootstocks. Seedlings coming from four populations from the Diospyros genus have been exposed to salt stress in order to identify salt tolerance genotypes within these populations. Morphological, physiological and transcriptomic approaches have revealed different mechanisms of tolerance among the population studied. An HKT1-like gene has been shown to have different root expression related to the salt tolerance phenotypes among and within populations. Additionally, we have observed differences in salt-responsive expression among PIP aquaporin genes. Genetic variability for salt tolerance can be generated in Diospyros species through crossings and used for overcome salt stress. Furthermore, differences in water use efficiency (WUE) have been obtained between and within populations. The information gathered at transcriptomic and physiological level demonstrated natural and heritable variability among Diospyros genus which is the key for salt-tolerant rootstock breeding programs.